From literacy to politicization in the Viva Deus Community - Betania Oliveira Barroso; Jullyana Cristhina Almeida de Freitas; Elena Steinhorst Damasceno; Juliana Ferreira de Sousa (Universidade Federal do Norte do Tocantins, 2020)
This paper aims to present a practical experience of Popular Education, considering its social, pedagogical and cultural importance in resistance processes, based on the conceptions of Paulo Freire and how this contributes to literacy processes in a context of popular struggle for land in the Viva Deus Community, located on the rice road in the city of Imperatriz/MA, which has the Teaching. Research and Extension Group in Popular Education - GEPEEP. In this sense, we will present two training fronts: EJA literacy and politicization, emphasizing literacy through Freirean methodology, which brings us the circle of culture and the generating word as basic elements for the formation. Thus, starting from a dialogic, democratic, emancipatory action that is not only bound up with the formative process of knowing how to read and write, but also with a reaffirmation of the identity of the community, of the autonomous existence itself in the social space, meaning and can affirm the concretization of changes and transformations of the Living God Community.